WANPRESTASI NELAYAN PENGGARAP KERAMBA IKAN DALAM PERJANJIAN BAGI HASIL DENGAN PEMILIK KERAMBA DI KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - NIM. A1011151198, IRSYAD MAULANA (Jurnal Fatwa Hukum, 2024)
Abstract Freshwater fish farming is currently in great demand by the community, this is because it can provide quite a decent profit. This freshwater fish farming business can be done using a pond system or a cage system. The pond system is different from the cage system. The cage system is more efficient in terms of cost compared to the pond system because it does not require land (soil). In addition, the cage system that uses floating net cages is a flexible cultivation tool, because if it is not used, the cage can be landed to maintain its safety and maintenance.Mempawah Hilir District is one of the districts in Mempawah Regency. Mempawah Hilir District is located along the coast and river. Given the location of Mempawah Hilir District along the river, it is considered very suitable for fish farming using the cage system by the community.Currently, people who are relatively well-off in Mempawah Hilir District have fish cages, but they are unable to work on their own cages. Therefore, the owners of these cages enter into agreements with other people (fishermen working on fish cages) to manage their fish cages by means of profit sharing or verbal fishery profit sharing agreements, because of mutual trust from the cage owners to the fisherman working on fish cages to manage their fish cages.However, in reality, the fisherman working on fish cages commits a breach of contract against the cage owners. The form of breach of contract committed by the fisherman working on fish cages is that when the fish are harvested, the fisherman working on fish cages does not inform the cage owners and the fisherman working on fish cages often takes fish without the knowledge of the cage owners, so that when the profit sharing is carried out, the cage owners do not get their rights of 70% (seventy percent) of the harvest, clearly the cage owners suffer losses.The factors causing the fisherman working on fish cages to commit a breach of contract are because it is not enough to cover the living expenses of the fisherman's family and the cage owners never or rarely check their cages because they are fully entrusted to the fisherman working on fish cages.The legal consequences for fishermen working on fish cages who default/break their promises to them in the fish profit sharing agreement are to pay compensation. In general, the calculation of the amount of compensation is based on an agreement between the fish cage owner and the fishermen working on the fish cage. In essence, the fish cage owner will not pressure and burden the fishermen working on the fish cage in paying compensation.The efforts made by the fish cage owner against the fishermen working on the fish cage who default in the fish profit sharing agreement are to hold family discussions. This is done because the fish cage owner still maintains good relations with the fishermen working on the fish cage, most of whom are still related and are local residents who have long been known by the fish cage owner. Keywords: Profit Sharing Agreement, Fish Cages, Default Abstrak Saat ini masyarakat yang tergolong mampu di Kecamatan Mempawah Hilir memiliki keramba ikan, namun mereka tidak sanggup untuk menggarap kerambanya sendiri. Oleh karena itu, para pemilik keramba ini menjalin perjanjian dengan orang lain (nelayan penggarap keramba ikan) untuk mengurus keramba ikannya dengan cara bagi hasil atau perjanjian bagi hasil perikanan secara lisan, karena saling percaya dari pemilik keramba terhadap nelayan penggarap keramba ikan untuk mengusahakan keramba ikannya. Namun dalam realitanya, nelayan penggarap keramba ikan melakukan wanprestasi terhadap pemilik keramba. Adapun bentuk wanprestasi yang dilakukan oleh nelayan penggarap keramba ikan adalah pada saat panen ikan, nelayan penggarap keramba ikan tidak memberitahukan kepada pemilik keramba dan nelayan penggarap keramba ikan seringkali mengambil ikan tanpa sepengetahuan pemilik keramba, sehingga pada saat dilakukan bagi hasil ternyata pemilik keramba tidak mendapatkan haknya sebesar 70% (tujuh puluh persen) dari hasil panen tersebut, jelas pemilik keramba mengalami kerugian.Faktor penyebab nelayan penggarap keramba ikan melakukan wanprestasi dikarenakan tidak mencukupi untuk biaya hidup bagi keluarga nelayan penggarap keramba ikan dan pemilik keramba tidak pernah atau jarang mengecek kerambanya karena dipercayakan secara penuh kepada nelayan penggarap keramba ikan. Akibat hukum bagi nelayan penggarap keramba ikan yang melakukan wanprestasi/ingkar janji terhadap mereka dalam perjanjian bagi hasil ikan adalah membayar ganti rugi. Pada umumnya, penghitungan besarnya ganti rugi berdasarkan kesepakatan antara pemilik keramba dengan nelayan penggarap keramba ikan. Intinya, pemilik keramba tidak akan menekan dan memberatkan nelayan penggarap keramba ikan dalam membayar ganti rugi. Upaya yang dilakukan oleh pemilik keramba terhadap nelayan penggarap keramba ikan yang melakukan wanprestasi dalam perjanjian bagi hasil ikan adalah melakukan musyawarah kekeluargaan. Hal ini dilakukan karena pemilik keramba masih menjaga hubungan baik dengan nelayan penggarap keramba ikan yang sebagian besar masih ada hubungan keluarga dan merupakan penduduk setempat yang sudah lama dikenal oleh pemilik keramba. Kata Kunci: Perjanjian Bagi Hasil, Keramba Ikan, Wanprestasi